The Price of Capital and the Real Rate of Interest - Dan Usher (Queen's University, Department of Economics, 1969)
Few subjects in economics have been more exhaustively discussed than the relation between productivity and thrift in the determination of the rate of interest, yet leading authors continue to hold markedly divergent views. This issue might be brought into focus in the following paper by considering a few important questions, which will be presented to the reader in the paper.
Keywords: 330